Enhancing regeneration and repair of long-distance peripheral nerve defect injuries with continuous microcurrent electrical nerve stimulation - Kong, Junjie; Teng, Cheng; Liu, Fenglan; Wang, Xuzhaoyu; Zhou, Yi; Zong, Ying; Wan, Zixin; Qin, Jun; Yu, Bin; Mi, Daguo; Wang, Yaxian (Frontiers in Neuroscience, 2024)
Peripheral nerve injuries, particularly long-distance deficits, pose significant challenges in clinical repair. This study explores the potential of continuous microcurrent electrical nerve stimulation (cMENS) as an adjunctive strategy for promoting regeneration and repair in long-distance peripheral nerve defects. First, we optimized cMENS parameters through a screening process, identifying a 10-day regimen of 100uA microcurrent stimulation as optimal. Subsequent evaluation focused on Schwann cell activity and the microenvironment, revealing cMENS's positive impact on maintaining the proliferation of denervated Schwann cells and enhancing the secretion of neurotrophic factors. In a rat model of sciatic nerve defect-bridge repair, cMENS demonstrated superior effects compared to control groups, promoting motor function recovery, nerve conduction, and sensory and motor neuron regeneration. Histological examinations revealed enhanced maturation of regenerated nerve fibers and reduced denervated muscle atrophy. While cMENS shows promise as an adjuvant treatment for long-distance nerve defects, future research should explore extended stimulation durations and potential synergies with tissue engineering grafts for improved outcomes. This study contributes comprehensive evidence supporting the efficacy of cMENS in enhancing peripheral nerve regeneration.